Production and Export of Shrimp of Bangladesh : Problems and Prospects (Progressive Agriculture, 2013)
A study on problems and prospects of shrimp production and marketing from Bangladesh on the basis of secondary information was carried out from July to October 08. Shrimp farming has emerged one of the important economic activities in Bangladesh and become the second largest export industry after garments. Shrimp aquaculture in coastal areas plays a major role providing employment, income and food security to remote coastal people where alternative livelihood options are limited. Shrimp culture system is extensive to improved extensive type with total production of 55000 mt of brackish water shrimp and 12000 mt of freshwater shrimp. In coastal Bangladesh, shrimp culture has led to many social and environmental problems. In export markets, shrimps are great but many challenges remain ahead because of increasing requirements of quality, food hygiene and development of technological and trade barriers in large shrimp markets in USA and EU countries. However, challenges lies with good aquaculture practice and competitive export, which are the effective tools for poverty alleviation and national development program for Bangladesh.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16868 Progress. Agric. 20(1 & 2): 163 171, 2009